Direct healthcare cost of pediatric systemic lupus erythematosus in the Philippines - Yee, Maria Kathryn Ramirez; Collante, Ma Theresa Moreno; Bernal, Christine Bea (Frontiers in Pediatrics, 2023)
Background: Pediatric rheumatic diseases are chronic illnesses that pose a huge economic burden to children and their families, one of the most common is pediatric Systemic Lupus Erythematosus (pSLE). Direct cost of pSLE has been studied in other countries. In the Philippines, this was only studied in the adult population. This study aimed to determine the direct cost of pSLE in the Philippines and its cost predictors Methods: A total of 100 pSLE patients were seen from November 2017 to January 2018 at the University of Santo Tomas. Informed consent and assent forms were obtained. A total of 79 patients met the inclusion criteria and parents were asked to answer the questionnaire. Data was tabulated and was subjected to statistical analysis. Cost predictors were estimated using a stepwise log linear regression. Results: A total of 79 pediatric SLE patients, with a mean age of 14.68 + 3.24, 89.9% of which were females, with a mean disease duration of 36.08 + 23.54, were included in this study. A total of 65.82% had lupus nephritis and 49.37% were in flare. The mean annual direct cost for pediatric SLE patient was 162,764.81php (USD 3,047.23). Majority of the expense comes from medications. Regression analysis showed that the predictors of increased cost in doctor’s fee in clinic visits (p-value 0.000) and IV infusion (p-value 0.01) were the higher combined income of the parents. Conclusion: This is a preliminary study on the mean annual direct cost of pediatric SLE patients in a single center in the Philippines. Pediatric SLE patients with nephritis and other target organ damage were seen to increase the cost up to 2 to 3.5x. Patients in flare also had a higher cost of up to 1.6x. Cost drivers in this study were the age and sex of the patient and the parent’s / caregiver’s combined income and educational attainment.